Cerebral Artery Vasoconstriction After Galcanezumab Loading Dose for Migraine Prevention: A Case Report - Thanin Asawavichienjinda; Nutchawan Jittapiromsak; Andrew Blumenfeld (Pain and Therapy)
Abstract Anti-calcitonin gene-related peptide (CGRP) monoclonal antibodies that target CGRP ligands or receptors, may cause a very rare side effect of reversible cerebral vasoconstriction syndrome (RCVS). This study is a case report of a patient who developed cerebral artery vasoconstriction documented on serial brain magnetic resonance angiography (MRA) scans without the typical manifestations of RCVS following galcanezumab loading dose. Case report: A 40-year-old female patient with high-frequency episodic migraine with visual aura on topiramate 100 mg/day developed transient numbness of the right upper and lower extremities and right face without headache and a normal neurological examination 10 min after a loading dose of galcanezumab, which resolved over the next 2 days. Magnetic resonance angiography brain imaging showed segmental arterial constriction of both middle cerebral arteries in the M1–2 segments and both posterior cerebral arteries in the P1–2 segments, which partial resolved in a subsequent study by the end of 6 months. There were no other supporting examination data, such as transcranial Doppler, which might provide additional information on the progression and improvement of the vasoconstriction. Her differential diagnosis included prolonged migraine sensory aura without headache, RCVS, or cerebral vasoconstriction secondary to the effect of an anti-CGRP monoclonal antibody. Further research needs to be conducted.